Temporal variability of lagoon–sea water exchange and seawater circulation through a Mediterranean barrier beach. (9th April 2019) - Tamborski, Joseph; van Beek, Pieter; Rodellas, Valentí; Monnin, Christophe; Bergsma, Erwin; Stieglitz, Thomas; Heilbrun, Christina; Cochran, J. Kirk; Charbonnier, Céline; Anschutz, Pierre; Bejannin, Simon; Beck, Aaron
Abstract: The subterranean flow of water through sand barriers between coastal lagoons and the sea, driven by a positive hydraulic gradient, is a net new pathway for solute transfer to the sea. On the sea side of sand barriers, seawater circulation in the swash‐zone generates a flux of recycled and new solutes. The significance and temporal variability of these vectors to the French Mediterranean Sea is unknown, despite lagoons constituting ~ 50% of the coastline. A one‐dimensional 224 Raex / 223 Ra reactive‐transport model was used to quantify water flow between a coastal lagoon (La Palme) and the sea over a 6‐month period. Horizontal flow between the lagoon and sea decreased from ~ 85 cm d −1 during May 2017 (0.3 m 3 d −1 m −1 of shoreline) to ~ 20 cm d −1 in July and was negligible in the summer months thereafter due to a decreasing hydraulic gradient. Seawater circulation in the swash‐zone varied from 10 to 52 cm d −1 (0.4–2.1 m 3  d −1 m −1 ), driven by short‐term changes in the prevailing wind and wave regimes. Both flow paths supply minor dissolved silica fluxes on the order of ~ 3–10 mmol Si d −1 m −1 . Lagoon–sea water exchange supplies a net dissolved inorganic carbon (DIC) flux (320–1100 mmol C d −1 m −1 ) two orders of magnitude greater than seawater circulation and may impact coastal ocean acidification. The subterranean flow of water through sand barriers represents a significant source of new DIC, and potentially other solutes, to the Mediterranean Sea during high lagoon water‐level periods and should be considered in seasonal element budgets.